An electrochemical DNA microbiosensor based on succinimide-modified acrylic microspheres - Ulianas, Alizar; Heng, Lee Yook; Sharina, Abu Hanifah; Tan, Ling Ling (MDPI, 2012)
An electrochemical microbiosensor for DNA has been fabricated based on new acrylic microspheres modified with reactive N-acryloxysuccinimide (NAS) functional groups. Hydrophobic poly(n-butylacrylate-N-acryloxysuccinimide) microspheres were synthesized in an emulsion form with a simple one-step photopolymerization technique. Aminated DNA probe was attached to the succinimde functional group of the acrylic microspheres via covalent bonding. The hybridization of the immobilized DNA probe with the complementary DNA was studied by differential pulse voltametry using anthraquninone-2-sulfonic acid monohydrate sodium salt (AQMS) as the electroactive hybridization label. The influences of many factors such as duration of DNA probe immobilization and hybridization, pH, type of ions, buffer concentrations, ionic strength, operational temperature and non-complementary DNA on the biosensor performance were evaluated. Under optimized conditions, the DNA microbiosensor demonstrated a linear response range to target DNA over a wide concentration range of 1.0 × 10−16 and 1.0 ´ 10−8 M with a lower limit of detection (LOD) of 9.46 ´ 10−17 M (R2 = 0.97). This DNA microbiosensor showed good reproducibility with 2.84% RSD (relative standard deviation) (n = 3). Application of the NAS-modified acrylic microspheres in the construction of DNA microbiosensor had improved the overall analytical performance of the resultant DNA microbiosensor when compared with other reported DNA biosensors using other nano-materials for membranes and microspheres as DNA immobilization matrices.